Aromatic interactions frontiers in knowledge and application - Johnson, Darren W.; Hof, Fraser (Monographs in supramolecular chemistry, 2017)
This book provides a wide ranging survey of the latest findings and advances surrounding aromatic interactions, from the fundamentals to modern applications